The Role Of Folklore In Dalit Literature - Santosh Suman (Revista Electronica de Veterinaria, 2024)
Folklore in Dalit literature serves as a powerful tool for reclaiming histories that have been marginalized or erased by dominant narratives. Dalit writers often draw upon oral traditions, myths, and folk tales to reconstruct a past that reflects their lived experiences and struggles. For example, writers like Namdeo Dhasal and Bama use folk songs and oral storytelling to highlight the resilience of Dalit communities against caste oppression. These narratives challenge mainstream historical accounts that often overlook the contributions and suffering of Dalits, thereby creating a counter-discourse that reclaims their rightful place in history.Beyond preserving historical truths, folklore in Dalit literature also fosters a sense of community and solidarity. Oral traditions, such as the telling of folktales or the singing of resistance songs, serve as a means of collective empowerment, strengthening communal bonds among Dalits. For instance, the Bhakti movement poets like Ravidas and Chokhamela infused their poetry with folk elements that spoke directly to the struggles of the oppressed, offering both spiritual and social liberation. Contemporary Dalit writers continue this tradition by integrating folk narratives into their works, ensuring that these cultural expressions remain relevant in modern struggles against caste discrimination.Furthermore, folklore significantly shapes the aesthetic and thematic aspects of contemporary Dalit literature. Many Dalit writers use folk motifs, proverbs, and storytelling structures to craft narratives that are deeply rooted in their cultural heritage. For example, Arjun Dangle and Sharankumar Limbale incorporate folktales and oral histories into their writings to emphasize themes of justice, dignity, and resistance. This integration not only enriches the literary landscape but also serves as a reminder of the enduring relevance of folklore in articulating Dalit identity and aspirations. Through these literary efforts, folklore becomes a dynamic force that bridges the past and present, ensuring that Dalit voices continue to challenge oppression and assert their cultural legacy.This paper explores how Dalit writers incorporate folklore in their narratives to challenge dominant historical accounts and create a counter-discourse. It examines the oral traditions, myths, songs, and storytelling practices that influence Dalit literary expressions, highlighting their significance in preserving historical truths, fostering community solidarity, and shaping contemporary Dalit literature.